Nitric oxide donors for peripheral artery disease. (April 2018) - Falconer, Debbie; Papageorgiou, Nikolaos; Salem, Karim; Lim, Wei Yao; Katsargyris, Athanasios; Avgerinos, Efthimios; Tousoulis, Dimitris
Highlights: Nitric oxide is a key mediator regulating vascular tone and angiogenesis. Aberrant production of NO is implicated in the development of PAD. Drugs that increase NO improve claudication. L-arginine has conflicting results. Abstract : Current management of peripheral arterial disease involves risk factor modification and revascularisation, but many patients are still left with debilitating symptoms. Therefore, new treatment strategies are needed. The importance of nitric oxide, and its role in regulating endothelial function, is well-established. Altering the nitric oxide pathway has been extensively studied as a means of treating vascular disease, including peripheral arterial disease. Statins and ACE inhibitors have been shown to enhance endogenous nitric oxide and improve intermittent claudication symptoms. Studies usingl -arginine have produced differing results, for reasons for yet fully understood. A greater understanding of the nitric oxide pathway, and its enzymatic control, has generated more potential therapeutic targets to alter NO levels.